Seventy-fourth Constitution Amendement Act and conformity legislation in Orissa for empowerment of municipal bodies an overview. - Mohanty, L.N.P. (1995)
"The paper gives a comparative account of provisions in the Orissa Municipal Act, 1950 and the new amendments introduced to bring it in conformity with the Constitution (Seventy Frourth Amendement) Act, 1992. It discusses some of the salient provisions relating to functions devolved to municipalities out of the Twelfth Schedule and to the Wards Committees. Dissolution of elected councils in the state two years before the expiry of their term of office and delaying the local elections, the paper argues, are not in conformity with democratic ethos which the Constitution Amendement intends to strengthen".
Keywords: India - Constitution - Amendments - 74th; Municipal government - India - Orissa; Local government